Political instability in the Muslim world: an analysis of regime type and party system - Md. , Moniruzzaman; Omar, Muhamad Fuzi (s.n, 2015)

(untitled)
Using the data sets of Fragile States Index (FIS) and the Peace and Conflict Instability Ledger (PCIL) over the past decade, this study has analyzed five types of regimes in the developing countries namely absolute monarchical regimes, authoritarian regimes, constitutional monarchical regimes, presidential regimes and parliamentary regimes. By looking at the relationship between these regime types and the party system at work in each of these countries this research has indicated that party system matters significantly in political stability and instability. In the case of absolute monarchies where no parties are allowed, they are politically much less unstable. All the authoritarian regimes practice one-party system, and they maintain comparatively high political stability. All the presidential regimes in this study maintain dominant party system amid many other parties at work, and majority of the regimes maintains a low degree of political instability. On the other hand, constitutional monarchies and parliamentary republican regimes operate under multi-party system, and both types of regimes experience relatively higher rate of political instability. Therefore, based on the evidence it is reasonable to conclude that it is not regime type but party system that matters more in political stability or instability. Key words: Political Instability, Muslim World, Party System, Regime Type